PENGARUH BLOK INDIVIDUAL BERBAHAN CERROBEND PADA DISTRIBUSI DOSIS SERAP BERKAS FOTON 6 MV LINEAR ACCELERATOR (LINAC) - Afrio Rika. R; Eko Hidayanto; Zaenal Arifin; Sanggam Ramantisan (Youngster Physics Journal, 2014)
Individual blocks were often used as accessories irradiation in radiotherapy to protect organs at risk (OR). Therefore, the study was examined distribution of absorbed dose on the phantom horizontal axis due to the effect of using individual blocks made of cerrobend with variations of individual blocks surface area  and variation form individual blocks divergent and non-divergent then determined whether exceeding the tolerance limit.The used of Irradiation technique was a Linear Accelerator (LINAC) with 6 MV photons at dmax of 1.5 cm with SSD 100 cm, wide field irradiation by 20 cm x 20 cm, with the considered organs protected by 10 cm x 10 cm. Individual block made of cerrobend was shaped divergent and non-divergent with variations of surface area projections by 9 cm x 9 cm, 9.5 cm x 9.5 cm and 10 cm x 10 cm.The use of divergent and non-divergent blocks at the Organ at Risk (OR) and irradiation target exceeded the tolerance limit of the absorbed dose was on the OR transmission dose over the maximum permitted limit of 5%, while the results obtained from the study ranged from 6,0% - 6.8%, on irradiation target results obtained ranged from 101.3% - 109.6% while the tolerance permitted by ICRU  (The International Commission on Radiation Units and Measurements) Report 62 was -5% and +7%. In the transition area doses below 50%, remained <50%. Moreover, the distribution dose on the divergent block was better than the non divergent.Keywords: Absorbed dose distribution, divergent block, non-divergent block, transmission dose, target dose, transition dose, cerrobend.